Design and analysis of conical rotary compressor. Issue 1 (1st November 2022) - Lu, Y; Hoang, K; Noake, D; Low, N
Abstract : Conical Rotary Compressor (CRC) is a screw type Positive Displacement Machine (PDM) consisting of one inner rotor rotating inside an outer rotor. The conical internal meshing rotors with the feature of variable pitch and rotor profile have an inherent capability to operation at high pressure ratio due to high built-in volume ratio and low leakage. CRC has potential to run in various applications such as Heating, Ventilation, and Air Conditioning (HVAC) system, vacuum pumps, and air compressors. The performance of the machine is heavily affected by rotor profile and rotor geometry. In this paper, non-parallel axis conical rotor is firstly introduced according to current successful design and manufacture practice, then parallel axis conical rotors are design based on meshing theory. Then, geometrical parameters such as meshing line length, cross section area, chamber volume and relative velocity are analysed. Finally, the experiments were conducted under different pressure ratio up to 26 and the volume flow rate, specific power, volumetric efficiency, and isentropic efficiency are compared. As a result of this study, CRC could maintain high level of volumetric and isentropic efficiency under wide range of pressure ratio. Improvement of the compressor design can be made to limit increases in temperature, reduce relative velocity and increase the overall efficiency of the machine.